The Decline of the Professions - Ohmann, Richard; Schrecker, Ellen (Radical Teacher, 2022)
The paradigm of an academic career- doctoral study, then a well charted ascent through the ranks, culminating in 25 or 30 or so years as a full professor, and tapering off with many years on an ample pension-was never guaranteed or anything like universal, but was a reasonable aspiration for a college graduate who loved physics or sociology or art history. Of those teaching in colleges and universities, around 75% are contingent workers: short contracts, no assurance of renewal, low pay, maybe health insurance but probably not, no pension fund, little if any say in faculty governance or in the making of curriculum, maybe no office and no phone, maybe several other jobs off the tenure track.